One‐Step Synthesis and High‐Efficiency Decoloration of Multifunctional Porous‐C/Fe3O4 Nanospheres by Using a Sandwich‐Structured Precursor with Three Roles. Issue 8 (21st June 2013) - Wang, Li‐Zu; Wen, Ming; Yuan, Pin‐Shi; Zhou, Linyi; Wu, Qing‐Sheng
Abstract A new strategy for the one‐step synthesis of multifunctional porous‐C/Fe3O4 nanospheres has been successfully developed by using ferrocenyl formic acid as a precursor. Based on its special structure, this sandwich structural precursor of ferrocenyl formic acid plays three roles in the synthesis process: it simultaneously serves as the carbon and iron source, templating agent, and pore‐forming agent. The proposed synthesis is corroborated by characterization through SEM, TEM, XRD, FTIR spectroscopy, Raman spectroscopy, BET surface area measurements, BJH distributions, and vibrating sample magnetometry. The average diameter of as‐synthesized porous‐C/Fe3O4 nanospheres is about 400 nm. Because of the porous structure of carbon nanospheres and its surface plasmon resonance with attached Fe3O4 nanoparticles, the as‐synthesized porous‐C/Fe3O4 nanospheres exhibit high activity toward the decoloration of rhodamine B. In addition, the resultant composites present ferromagnetic behavior with a magnetization saturation of 13.76 emu g−1, can be easily separated and recycled by an external magnet field for use in a variety of applications.